2020
DOI: 10.31235/osf.io/hxjk5
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Apolitical Values & Compliance with Government-Recommended Prosocial Health Behavior

Abstract: At the start of the COVID-19 pandemic, federal government and local governments across the U.S. recommended that individuals engage in social distancing and other prosocial health behaviors (e.g., wear a mask when out in public). While social scientists know a fair amount about the extent to which people complied with these recommendations, far less is known about why some people may have been more likely to do so. Building on insights from Human Values Theory, we argue that people who are more self-transcende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…A previous study encouraging influenza vaccination found that individuals exposed to pro-social messages-in the form of describing potential flu victims who could have serious adverse effects if others do not vaccinate-were more likely to intend to vaccinate; , including those who had previously refused to vaccinate (Li et al, 2016). Similarly, those who are more self-transcendent (more likely to put others' needs before their own) are more likely to engage in social distancing measures to prevent the spread of COVID-19 (Motta and Goren, 2020; see also; Van der Linden et al, 2020).…”
Section: Overcoming Vaccine Hesitancy Through Effective Health Communication How Personal Economic and Collective Health Risk Frames Coulmentioning
confidence: 99%
“…A previous study encouraging influenza vaccination found that individuals exposed to pro-social messages-in the form of describing potential flu victims who could have serious adverse effects if others do not vaccinate-were more likely to intend to vaccinate; , including those who had previously refused to vaccinate (Li et al, 2016). Similarly, those who are more self-transcendent (more likely to put others' needs before their own) are more likely to engage in social distancing measures to prevent the spread of COVID-19 (Motta and Goren, 2020; see also; Van der Linden et al, 2020).…”
Section: Overcoming Vaccine Hesitancy Through Effective Health Communication How Personal Economic and Collective Health Risk Frames Coulmentioning
confidence: 99%
“…A previous study encouraging influenza vaccination found that individuals exposed to pro-social messages-in the form of describing potential flu victims who could have serious adverse effects if others do not vaccinate-were more likely to intend to vaccinate; , including those w h oh a dp r e v i o u s l yr e f u s e dt ov a c c i n a t e ( Li et al, 2016). Similarly, t h o s ew h oa r em o r es e l f -t r a n s c e n d e n t( m o r el i k e l yt op u to t h e r s ' needs before their own) are more likely to engage in social distancing measures to prevent the spread of COVID-19 (Motta and Goren, 2020;s e ea l s o ;Van der Linden et al, 2020).…”
Section: Overcoming Vaccine Hesitancy Through Effective Health Commun...mentioning
confidence: 99%